Composite material and preparation method thereof, negative pole piece and preparation method thereof, diaphragm-free battery, lithium metal battery and electric equipment

By introducing lithium-philic metal materials, two-dimensional layered materials and carbon materials into the composite materials of lithium metal batteries, a lithium-philic gradient is formed, and the problem of uneven nucleation of lithium is solved, achieving uniform distribution of lithium metal and improving battery performance.

CN119920858APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411461994.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The lithium-reducing properties of existing lithium metal negative electrode materials lead to uneven nucleation of lithium, forming isolated large crystal nucleations, which in turn leads to the formation of lithium dendrites and dead lithium, affecting battery performance and increasing safety hazards.

Method used

By introducing lithium-philic metal materials, two-dimensional layered materials and carbon materials into the composite materials, a lithium-philic gradient is formed, which improves the lithium-philicity of the composite materials, promotes the uniform nucleation and distribution of lithium metals, and provides more lithium-philic active defect sites through the heterogeneous interface between the two-dimensional layered materials and carbon materials, improving the efficiency of reversible lithium deposition.

Benefits of technology

The uniform nucleation and distribution of lithium metal is achieved, the formation of lithium dendrites and dead lithium is inhibited, and the coulombic efficiency, safety performance and circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920858A_ABST
    Figure CN119920858A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a negative pole piece and a preparation method thereof, a diaphragm-free battery, a lithium metal battery and electric equipment. The composite material comprises a two-dimensional layered material, a carbon material and a lithium-loving metal material, wherein the two-dimensional layered material comprises sulfide of transition metal and / or nitride of transition metal, the lithium-loving metal material is at least distributed on the two-dimensional layered material, and the carbon material is at least coated on the surface of the two-dimensional layered material. The composite material disclosed by the invention is high in lithium affinity, can realize preferential nucleation of lithium metal, enables a surface electric field and ion distribution to be homogenized, effectively inhibits lithium dendrites and dead lithium, and further facilitates improvement of coulombic efficiency, safety performance and cycle performance of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of new energy technology, and specifically relates to a composite material and a preparation method thereof, a negative electrode plate and a preparation method thereof, a diaphragm-free battery, a lithium metal battery and electrical equipment. Background Art

[0002] In the related art, carbon materials are usually selected as carriers of lithium metal negative electrodes due to their excellent electrical conductivity. However, the lithium-repellent nature of carbon materials limits the uniform nucleation of lithium. The nucleation barrier of lithium metal on carbon materials is very large, and the deposited lithium on them presents isolated and large crystal nuclei. The uneven nucleation and growth of lithium metal leads to the formation of uncontrollable lithium dendrites and dead lithium (inactive lithium) and even electrode pulverization, which may pierce the diaphragm and cause short circuit and thermal runaway, especially for batteries without diaphragms, which are more likely to cause safety hazards and affect battery performance. Summary of the invention

[0003] In view of the above-mentioned defects or deficiencies in the prior art, it is desired to provide a composite material and a preparation method, a negative electrode plate and a preparation method, a diaphragm-free battery, a lithium metal battery and an electrical device, wherein a lithium-affinity gradient is formed by a lithium-affinity metal material, a two-dimensional layered material and a carbon material, which is beneficial to improving the lithium-affinity of the composite material and realizing the preferential nucleation and uniform distribution of lithium metal; and the heterogeneous interface between the two-dimensional layered material and the carbon material provides lithium-affinity active defect sites, which is beneficial to improving the efficiency of reversible lithium deposition, and the carbon material can also improve the conductivity, thereby helping to improve the coulombic efficiency, safety performance and cycle performance of the battery.

[0004] In a first aspect, the present invention provides a composite material for a lithium metal battery, comprising: a two-dimensional layered material, a carbon material, and a lithium-philic metal material;

[0005] The two-dimensional layered material includes transition metal sulfides and / or transition metal nitrides, the lithium-philic metal material is at least distributed on the two-dimensional layered material, and the carbon material is at least coated on the surface of the two-dimensional layered material.

[0006] As an optional option, the two-dimensional layered material includes at least one of MoS2, TiS2, VS2, WS2, Bi2S3, Ga2N3, Ti2N3, and W2N3.

[0007] As an optional solution, the mass ratio of the two-dimensional layered material to the carbon material is (60%-90%):(40%-10%).

[0008] As an option, the lithiophilic metal material includes Ag atom clusters.

[0009] In a second aspect, the present invention provides a method for preparing the composite material of the first aspect, the preparation method comprising:

[0010] The two-dimensional layered material and the carbon material precursor are mixed and heat treated to obtain a first product; wherein the two-dimensional layered material comprises a transition metal sulfide and / or a transition metal nitride;

[0011] The first product is immersed in a lithiophilic metal salt solution, and a reducing agent is added to reduce the lithiophilic metal ions to obtain a composite material.

[0012] In a third aspect, the present invention provides a negative electrode plate, comprising a current collector, lithium metal and the composite material of the first aspect, wherein the composite material and the lithium metal are arranged on the surface of the current collector.

[0013] As an optional solution, the thickness of the composite material on the surface of the current collector is 100 nm-10 μm.

[0014] As an optional solution, the thickness of lithium metal on the surface of the current collector is 0.01 μm-30 μm;

[0015] As an option, the lithium metal is distributed in the pores and / or on the surface of the composite material.

[0016] As an optional solution, a graphene layer is also included, and the graphene layer covers the surface of the composite material and / or the surface of the current collector.

[0017] As an option, the thickness of the graphene layer is 10 nm-5 μm.

[0018] In a fourth aspect, the present invention provides a method for preparing a negative electrode sheet, comprising:

[0019] The composite material of the first aspect or the composite material prepared according to the preparation method of the second aspect is arranged on a current collector, and lithium metal is loaded thereon to obtain a negative electrode sheet;

[0020] Alternatively, a two-dimensional layered material and a carbon material precursor are mixed and heat treated to obtain a first product; wherein the two-dimensional layered material includes a transition metal sulfide and / or a transition metal nitride, and the current collector attached with the first product is immersed in a lithium-philic metal salt solution, a reducing agent is added to reduce the lithium-philic metal ions, and lithium metal is loaded to obtain a negative electrode sheet.

[0021] As an optional solution, the two-dimensional layered material and the carbon material precursor are mixed and then heat-treated to obtain a first product, including:

[0022] mixing the template material and the two-dimensional layered material to obtain a hybrid material;

[0023] The mixed material and the carbon material precursor are mixed, heat treated, and the template material is etched with an acid solution or an alkali solution to obtain a first product.

[0024] As an optional scheme, after the two-dimensional layered material and the carbon material precursor are mixed, in the process of heat treating to obtain the first product, the heat treatment temperature is 400°C-800°C, and the heat treatment time is 0.5h-4h.

[0025] As an optional solution, during the process of immersing the current collector to which the first product is attached in the lithiophilic metal salt solution, the immersion time is 1 hour to 12 hours.

[0026] As an optional solution, the lithiophilic metal salt solution includes a silver nitrate solution, and the reducing agent includes at least one of sodium borohydride, potassium borohydride, hypophosphorous acid, sodium hypophosphite and formaldehyde.

[0027] As an optional solution, the carbon material precursor includes at least one of polydopamine, polypyrrole, poly(3,4-ethylenedioxythiophene), polyglucose and polyvinylpyrrolidone.

[0028] As an optional solution, after the composite material is disposed on the current collector, or after the current collector to which the first product is attached is immersed in a lithiophilic metal salt solution, and a reducing agent is added to reduce the lithiophilic metal ions, the method further comprises:

[0029] A graphene layer is deposited, the graphene layer covering the composite material and / or the current collector.

[0030] Optionally, depositing the graphene layer comprises:

[0031] A graphene layer is obtained by chemical vapor deposition of a carbon source in an auxiliary gas atmosphere; wherein the carbon source includes at least one of methane, acetylene, ethylene, carbon-containing polymer materials and anhydrous ethanol, and the auxiliary gas includes hydrogen, argon or nitrogen; the deposition temperature is 500°C-800°C, and the deposition time is 10min-2h.

[0032] In a fifth aspect, the present invention provides a diaphragm-free battery, comprising the negative electrode plate of the third aspect or the negative electrode plate prepared according to the method of the fourth aspect.

[0033] In a sixth aspect, the present invention provides a lithium metal battery, comprising the negative electrode plate of the third aspect or the negative electrode plate prepared according to the preparation method of the fourth aspect.

[0034] In a seventh aspect, the present invention provides an electrical device, comprising the diaphragm-free battery or lithium metal battery of the fifth aspect, and the diaphragm-free battery or lithium metal battery supplies power to the electrical device.

[0035] The composite material provided by the present invention forms a lithium-philic gradient through a lithium-philic metal material, a two-dimensional layered material and a carbon material, thereby improving the lithium-philicity of the composite material. On the one hand, the lithium-philic metal material is distributed on the two-dimensional layered material, the two-dimensional layered material has a lithium-philic sulfur element or a nitrogen element, lithium metal is preferentially nucleated on the lithium-philic metal material, and the carbon material is second. The two-dimensional layered material serves as a skeleton, which can reliably support lithium metal and alleviate the volume change of lithium, thereby making the surface electric field and ion distribution uniform, and effectively inhibiting lithium dendrites and dead lithium. On the other hand, the heterogeneous interface between the two-dimensional layered material and the carbon material can also provide more lithium-philic active defect sites, which is beneficial to improving the efficiency of reversible lithium deposition. On the other hand, coating the two-dimensional layered material with a carbon material to form a three-dimensional structure can effectively improve the conductivity of the composite material, and at the same time, the carbon material can also effectively alleviate the volume expansion of lithium deposition, thereby helping to improve the coulombic efficiency, safety performance and cycle performance of lithium metal batteries, especially diaphragm-free batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:

[0037] Figure 1 This is a scanning electron microscope image of the negative electrode sheet after the battery cycle test of Example 4 of the present application is completed;

[0038] Figure 2 This is a scanning electron microscope image of the negative electrode sheet of Example 4 of the present application before assembling the battery. DETAILED DESCRIPTION

[0039] The present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention.

[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail with reference to the embodiments below.

[0041] In a first aspect, an embodiment of the present application provides a composite material for a lithium metal battery, comprising: a two-dimensional layered material, a carbon material, and a lithium-philic metal material;

[0042] Among them, the two-dimensional layered material includes transition metal sulfides and / or transition metal nitrides, the lithium-philic metal material is at least distributed on the two-dimensional layered material, and the carbon material is at least coated on the surface of the two-dimensional layered material; the sulfur element and nitrogen element in the two-dimensional layered material are lithium-philic elements, which are beneficial to improving the lithium-philicity of the composite material.

[0043] It can be understood that the carbon material can be but is not limited to graphite, graphene, porous carbon, carbon nanotubes, etc.; the lithiophilic metal material can be a lithiophilic metal atom, such as but not limited to palladium atoms, platinum atoms, gold atoms, silver atoms, nickel atoms, cobalt atoms, magnesium atoms and zinc atoms, etc., or the lithiophilic metal material can also be a lithiophilic metal alloy, such as but not limited to an alloy of at least two of palladium, platinum, ruthenium, gold, silver, nickel, cobalt, magnesium and zinc.

[0044] In some embodiments, the two-dimensional layered material has defect sites, which are beneficial to the deposition of lithiophilic metal materials, thus facilitating the uniform nucleation and distribution of lithium metal; wherein the defect sites may be, but are not limited to, pore structures, functional groups (such as hydroxyl groups, carboxyl groups, etc.) or heterogeneous interfaces, etc.

[0045] It can also be understood that the lithium-philic metal material can be distributed on the two-dimensional layered material. Of course, the lithium-philic metal material can also be distributed on the two-dimensional layered material and the carbon material at the same time, forming a heterogeneous interface between the two-dimensional layered material and the lithium-philic metal material; the carbon material can only coat the two-dimensional layered material, and the carbon material can also coat the two-dimensional layered material and the lithium-philic metal material at the same time. The embodiments of the present application are not limited to this. In the embodiments of the present application, due to the coating of the carbon material, a heterogeneous interface exists between the carbon material and the two-dimensional layered material, which is beneficial to provide defect sites for lithium metal deposition.

[0046] The composite material of the embodiment of the present application solves the problem that the lithium affinity difference of the negative electrode material in the prior art causes the uneven nucleation and growth of lithium metal, thereby causing lithium dendrites and dead lithium, affecting the battery performance. The composite material of the embodiment of the present application forms a lithium affinity gradient through lithium affinity metal materials, two-dimensional layered materials and carbon materials to improve the lithium affinity of the composite material; on the one hand, the lithium affinity metal material is distributed on the two-dimensional layered material, lithium metal is preferentially nucleated on the lithium affinity metal material, and the carbon material is second, and the two-dimensional layered material as a skeleton can reliably support lithium metal and alleviate the volume change of lithium, so that the surface electric field and ion distribution are uniform, and lithium dendrites and dead lithium are effectively inhibited; on the other hand, the heterogeneous interface between the two-dimensional layered material and the carbon material can also provide more lithium affinity active defect sites, which is beneficial to improve the efficiency of reversible lithium deposition; on the other hand, the carbon material is coated with the two-dimensional layered material to form a three-dimensional structure, which can effectively improve the conductivity of the composite material, and the carbon material can also effectively alleviate the volume expansion of lithium deposition, thereby improving the coulombic efficiency and cycle performance of the battery.

[0047] As a feasible approach, the two-dimensional layered material includes at least one of MoS2, TiS2, VS2, WS2, Bi2S3, Ga2N3, Ti2N3, and W2N3.

[0048] The raw materials of the two-dimensional layered material in this embodiment are easily available and have good lithium affinity. Its two-dimensional layered structure is conducive to the uniform distribution of lithium-philic metal materials, and further conducive to the uniform distribution and nucleation of lithium metal.

[0049] In some other embodiments, the two-dimensional layered material may also be at least one of BN, g-C3N4 and Si3N4.

[0050] In a preferred embodiment, the mass ratio of the two-dimensional layered material to the carbon material is (60%-90%):(40%-10%).

[0051] The mass ratio of the two-dimensional layered material and the carbon material in this embodiment is conducive to ensuring that the two-dimensional layered material serves as a skeleton structure, thereby reliably supporting lithium metal and alleviating the volume change of lithium.

[0052] Specifically, the mass ratio of the two-dimensional layered material to the carbon material can be, but is not limited to, 60%:40%, 70%:30%, 75%:25%, 80%:20%, 85%:15% or 90%:10%, etc.

[0053] As a preferred embodiment, the lithiophilic metal material includes Ag atomic clusters.

[0054] The Ag atom clusters in this embodiment have good lithium affinity, and the precursor raw materials of the Ag atom clusters are easily available, simple to prepare, and low in cost.

[0055] In actual use, Ag atomic clusters are evenly distributed on the two-dimensional layered material. Since Ag atomic clusters have good lithium affinity, this is conducive to the uniform and preferential nucleation of lithium metal on them, and reliably suppresses lithium dendrites and dead lithium phenomena.

[0056] In summary, the composite material of the embodiment of the present application forms a lithium-philic gradient through lithium-philic metal materials, two-dimensional layered materials and carbon materials, thereby improving the lithium-philicity of the composite material; on the one hand, the lithium-philic metal material is distributed on the two-dimensional layered material, lithium metal is preferentially nucleated on the lithium-philic metal material, followed by the carbon material, and the two-dimensional layered material serves as a skeleton, which can reliably support lithium metal and alleviate the volume change of lithium, thereby making the surface electric field and ion distribution uniform, and effectively inhibiting lithium dendrites and dead lithium; on the other hand, the heterogeneous interface between the two-dimensional layered material and the carbon material can also provide more lithium-philic active defect sites, which is beneficial to improving the efficiency of reversible lithium deposition; on the other hand, coating the two-dimensional layered material with a carbon material to form a three-dimensional structure can effectively improve the conductivity of the composite material, and at the same time, the carbon material can also effectively alleviate the volume expansion of lithium deposition, thereby helping to improve the coulombic efficiency and cycle performance of the battery;

[0057] Furthermore, the two-dimensional layered materials and lithiophilic metal materials of the embodiments of the present application have readily available raw materials, low cost, and good lithiophilicity.

[0058] In a second aspect, an embodiment of the present application provides a method for preparing the composite material of the first aspect, the preparation method comprising:

[0059] The two-dimensional layered material and the carbon material precursor are mixed and heat treated to obtain a first product; wherein the two-dimensional layered material includes a transition metal sulfide and / or a transition metal nitride;

[0060] The first product is immersed in a lithium-philic metal salt solution, and a reducing agent is added to reduce the lithium-philic metal ions to obtain a composite material.

[0061] In a third aspect, an embodiment of the present application provides a negative electrode plate, comprising a current collector, lithium metal and the composite material of the first aspect, wherein the composite material and the lithium metal are arranged on the surface of the current collector.

[0062] It is understood that the composite material can be disposed on the surface of the current collector in any manner, such as but not limited to dry / wet coating, spraying, electrospinning or chemical vapor deposition.

[0063] The current collector may be copper foil or aluminum foil, etc. In a preferred embodiment, the current collector of the negative electrode is usually copper foil.

[0064] The composite material may be disposed on one surface or both surfaces of the current collector, which is not specifically limited in the embodiments of the present application.

[0065] As an achievable manner, the thickness of the composite material on the surface of the current collector is 1 μm-100 μm.

[0066] Specifically, the thickness of the composite material on the surface of the current collector may be, but is not limited to, 1 μm, 10 μm, 30 μm, 50 μm, 80 μm or 100 μm.

[0067] In this embodiment, the thickness range of the composite material is conducive to ensuring that the electrolyte can reliably infiltrate the composite material, while having a suitable lithium ion transmission channel, thereby improving the battery performance of the battery.

[0068] In some embodiments, the thickness of the lithium metal on the surface of the current collector is 0.01 μm-30 μm;

[0069] In other embodiments, the lithium metal is distributed in the pores and / or on the surface of the composite material.

[0070] As an achievable manner, a graphene layer is also included, and the graphene layer covers the surface of the composite material and / or the surface of the current collector.

[0071] It can be understood that the graphene layer can be on the area covering the surface of the composite material and the surface of the current collector where the composite material is not provided after the composite material is provided on the current collector, that is, the graphene layer is located above the composite material layer; of course, in some embodiments, the graphene layer can also be distributed between the composite material layer and the current collector surface, that is, the graphene layer first covers the current collector surface, and then the composite material layer covers the composite material layer. This is conducive to constructing a three-dimensional structure of the current collector, and then is conducive to improving the capacity of lithium ions.

[0072] As an achievable manner, the thickness of the graphene layer is 10 nm-5 μm.

[0073] Specifically, the thickness of the graphene layer can be but is not limited to 10nm, 100nm, 500nm, 1000nm, 2μm, 3μm, 4μm or 5μm; when the thickness of the graphene layer is less than 10nm, the lithium ion capacity cannot be reliably improved. When the thickness of the graphene layer is greater than 5μm, the thickness of the entire negative electrode sheet is too large, the electrolyte wettability is poor and the lithium ion transmission path is extended, thereby reducing the battery performance.

[0074] It is understandable that the negative electrode plate of the embodiment of the present application has all the characteristics and advantages of the above-mentioned composite material. In short, the negative electrode plate of the embodiment of the present application has a three-dimensional structure and high lithium affinity, which is conducive to the uniform deposition and nucleation of lithium metal, thereby reliably suppressing lithium dendrites and dead lithium phenomena, and improving lithium ion capacity and reversible lithium deposition efficiency. The three-dimensional structure can effectively suppress the volume expansion of lithium, which is conducive to improving the coulombic efficiency, safety performance and cycle performance of the battery.

[0075] In the embodiments of the present application, the lithium-philic gradient skeleton formed by the two-dimensional layered material, carbon material, and lithium-philic metal material can preferentially deposit lithium inside the pore structure, which plays a positive role in alleviating the volume change of lithium, regulating the distribution of lithium ions, and forming a stable SEI layer, greatly improving the overall space utilization of the skeleton, which is of great significance to the development of lithium metal batteries with high energy density and long cycle life.

[0076] In a third aspect, an embodiment of the present application provides a method for preparing a negative electrode sheet, comprising:

[0077] The composite material of the first aspect or the composite material prepared by the preparation method of the second aspect is arranged on a current collector, and lithium metal is loaded thereon to obtain a negative electrode sheet;

[0078] Alternatively, a two-dimensional layered material and a carbon material precursor are mixed and heat treated to obtain a first product; wherein the two-dimensional layered material includes a transition metal sulfide and / or a transition metal nitride, the current collector to which the first product is attached is immersed in a lithium-philic metal salt solution, a reducing agent is added to reduce the lithium-philic metal ions, and lithium metal is loaded to obtain a negative electrode sheet.

[0079] Among them, the carbon material precursor can be but is not limited to polydopamine (PDA), polypyrrole (PPY), poly(3,4-ethylenedioxythiophene) (PEDOT), polyglucose and polyvinylpyrrolidone (PVP) and the like; the carbon material precursor in the embodiment of the present application is a high-quality carbon material precursor and can reliably coat the two-dimensional layered material. After heat treatment, the carbon material precursor is carbonized to obtain a two-dimensional layered material coated with a carbon material;

[0080] The two-dimensional layered material and the carbon material precursor may be mixed by any method, such as but not limited to ball milling, liquid phase polymerization, etc., and the embodiments of the present application do not specifically limit this.

[0081] It can be understood that the first product is a two-dimensional layered material coated with carbon material. The coating of carbon material improves the conductivity of the two-dimensional layered material. At the same time, the first product has a three-dimensional structure, which can inhibit the volume expansion of lithium ions during the deposition process.

[0082] Among them, the lithiophilic metal salt solution can be but is not limited to a nitrate solution, a hydrochloride solution, a sulfate solution or other organic or inorganic acid salt solutions. The embodiments of the present application do not make specific limitations on this, as long as the raw materials are easily available and can reliably allow the lithiophilic metal ions to be deposited on the first product.

[0083] The reducing agent is mainly used to reduce the lithiophilic metal ions into lithiophilic metal atoms, so that the lithiophilic metal material is distributed on the first product in the form of atoms, which is beneficial to the uniform nucleation of lithium metal.

[0084] It can also be understood that the above-mentioned composite material or the first product can be attached to the current collector by dry / wet coating, spraying or electrospinning.

[0085] The preparation method of the negative electrode plate of the present embodiment is simple to operate. By first mixing the two-dimensional layered material and the carbon precursor and subjecting them to a heat treatment, it is beneficial to form a two-dimensional layered material coated with a carbon material with a three-dimensional structure. The heterogeneous interface between the carbon material and the two-dimensional layered material is beneficial to providing defect sites. The lithium-philic metal material is preferentially and evenly distributed on the two-dimensional layered material, thereby improving the lithium-philicity and conductivity of the negative electrode plate, thereby improving the battery performance.

[0086] As an achievable method, after mixing the two-dimensional layered material and the carbon material precursor, heat-treating to obtain a first product, the method comprises:

[0087] mixing the template material and the two-dimensional layered material to obtain a hybrid material;

[0088] The mixed material and the carbon material precursor are mixed, heat treated, and the template material is etched with an acid solution or an alkali solution to obtain a first product.

[0089] The template material may be any template agent, such as but not limited to silicon dioxide, molecular sieve, or aluminum oxide; the acid or alkali solution may be but not limited to sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, acetic acid, sodium hydroxide, potassium hydroxide or lithium hydroxide.

[0090] In this embodiment, the template method is used to facilitate the manufacture of defect sites on the two-dimensional layered material. The defect sites may be, but are not limited to, holes, accumulation of the two-dimensional layered material structure itself, and the like.

[0091] In some embodiments, in the process of mixing the two-dimensional layered material and the carbon material precursor and heat treating them to obtain the first product, the heat treatment temperature is 400° C.-800° C. and the heat treatment time is 0.5 h-4 h.

[0092] In the actual processing process, the two-dimensional layered material is mixed with aluminum oxide to obtain a mixture, the mixture is ball-milled with a carbon material precursor, and the temperature is raised from room temperature to a heat treatment temperature under an inert atmosphere and maintained for a predetermined time to carbonize the carbon material precursor.

[0093] Specifically, the temperature of the heat treatment can be but is not limited to 400°C, 500°C, 600°C, 700°C or 800°C; when the temperature of the heat treatment is lower than 400°C, the temperature of the heat treatment is too low and the carbon material precursor cannot be fully carbonized; when the temperature of the heat treatment is higher than 800°C, the temperature is relatively high, and on the one hand, the energy consumption is high, and on the other hand, the higher temperature may destroy the structure of the two-dimensional layered material itself.

[0094] Specifically, the heat treatment time is 0.5h, 1h, 2h, 3h or 4h, etc. When the heat treatment time is less than 0.5h, the heat treatment time is too short and the carbon material precursor cannot be fully carbonized; when the heat treatment temperature is higher than 4h, the heat treatment time is too long, which prolongs the experimental time and reduces production efficiency.

[0095] The heat treatment temperature and time of this embodiment are conducive to ensuring reliable carbonization of the carbon material precursor, while improving production efficiency and reducing production costs.

[0096] In some embodiments, during the process of immersing the current collector with the first product attached thereto in the lithiophilic metal salt solution, the immersion time is 1 hour to 12 hours.

[0097] The immersion time in this embodiment is conducive to the attachment of lithiophilic metal ions to the two-dimensional layered material, and is conducive to the construction of lithiophilic active sites.

[0098] Specifically, the soaking time may be, but is not limited to, 1 h, 3 h, 5 h, 7 h, 10 h or 12 h, etc.

[0099] In a preferred embodiment, the lithiophilic metal salt solution comprises a silver nitrate solution, and the reducing agent comprises at least one of sodium borohydride, potassium borohydride, hypophosphorous acid, sodium hypophosphite and formaldehyde.

[0100] As an achievable manner, after attaching the composite material to the current collector, or after immersing the current collector attached with the first product in a lithiophilic metal salt solution and adding a reducing agent to reduce the lithiophilic metal ions, the method further comprises:

[0101] A graphene layer is deposited, the graphene layer covering the composite material and / or the current collector.

[0102] In some embodiments, depositing the graphene layer includes:

[0103] A graphene layer is obtained by chemical vapor deposition of a carbon source in an auxiliary gas atmosphere; wherein the carbon source includes at least one of methane, acetylene, ethylene, carbon-containing polymer materials and anhydrous ethanol, and the auxiliary gas includes hydrogen, argon or nitrogen; the deposition temperature is 500°C-800°C, and the deposition time is 10min-2h.

[0104] In this embodiment, the graphene layer is obtained by in-situ growth, and the graphene layer is conducive to constructing a three-dimensional structure of the current collector, which is conducive to improving the lithium ion capacity.

[0105] In a fifth aspect, the present invention provides a diaphragm-free battery, comprising the negative electrode sheet of the third aspect or the negative electrode sheet prepared according to the method for preparing the negative electrode sheet of the fourth aspect. Thus, the diaphragm-free battery has all the features and advantages of the negative electrode sheet or the method for preparing the negative electrode sheet described above, which will not be repeated here. In general, the diaphragm-free battery has high coulombic efficiency, good safety and excellent cycle performance.

[0106] In a sixth aspect, the present invention provides a lithium metal battery, comprising the negative electrode sheet of the third aspect or a negative electrode sheet prepared according to the preparation method of the negative electrode sheet of the fourth aspect.

[0107] Therefore, the lithium metal battery has all the characteristics and advantages of the negative electrode sheet or the method for preparing the negative electrode sheet described above, which will not be repeated here. In general, the lithium metal battery has high coulombic efficiency, good safety and excellent cycle performance.

[0108] It is understandable that the battery may be a lithium-ion battery, a solid oxide battery, etc., and the embodiments of the present application do not specifically limit this.

[0109] In a seventh aspect, the present invention provides an electrical device, comprising the diaphragm-free battery of the fifth aspect or the lithium metal battery of the sixth aspect, wherein the diaphragm-free battery or the lithium metal battery supplies power to the electrical device.

[0110] Therefore, the electrical equipment has all the characteristics and advantages of the battery mentioned above, which will not be repeated here.

[0111] Specifically, the electrical device may be an electric vehicle, a hybrid vehicle, or an intelligent terminal device (such as but not limited to a mobile phone), etc.

[0112] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0113] Example 1

[0114] Preparation of negative electrode sheet:

[0115] Step 1, after ball milling MoS2 and polydopamine in a mass ratio of 80%:20%, the temperature was raised to 400°C in a nitrogen atmosphere and maintained for 30 minutes to carbonize the polydopamine to obtain a first product;

[0116] Step 2, soaking the first product in a silver nitrate solution, leaving it to stand for 1 hour, adding a reducing agent, sodium borohydride, to reduce the silver ions to silver atomic clusters, and washing with alcohol and water for multiple times, and then drying to obtain a composite material;

[0117] Step 3: coating the composite material on copper foil, and loading lithium metal on the copper foil by calendering, with a coating thickness of 1 μm, drying and cutting to obtain a negative electrode sheet.

[0118] Preparation of lithium battery:

[0119] The above-mentioned negative electrode plate, lithium iron phosphate (LiFePO4) positive electrode, separator, and electrolyte are assembled into a button battery in a glove box.

[0120] Example 2

[0121] Step 1, after ball milling MoS2 and polydopamine in a mass ratio of 90%:10%, the temperature was raised to 400°C in a nitrogen atmosphere and maintained for 30 minutes to carbonize the polydopamine to obtain a first product;

[0122] Step 2, coating the first product on copper foil with a coating thickness of 1 μm;

[0123] Step 3: Immerse the copper foil coated with the first product in a silver nitrate solution, let it stand for 1 hour, add the reducing agent sodium borohydride to reduce the silver ions to silver atomic clusters, and after multiple alcohol and water washings, load lithium metal on the copper foil by rolling, dry and cut to obtain a negative electrode sheet.

[0124] Example 3

[0125] Step 1, after mixing aluminum oxide and MoS2, and then mixing with polydopamine by ball milling (wherein the mass ratio of MoS2 to polydopamine is 90%:10%), heating to 400°C in a nitrogen atmosphere and maintaining for 30 minutes to carbonize the polydopamine to obtain a mixed material, placing the mixed material in a sodium hydroxide solution to remove aluminum oxide, and obtaining a first product;

[0126] Step 2, coating the first product on copper foil with a coating thickness of 1 μm;

[0127] Step 3: Immerse the copper foil coated with the first product in a silver nitrate solution, let it stand for 1 hour, add the reducing agent sodium borohydride to reduce the silver ions to silver atomic clusters, and after multiple alcohol and water washings, load lithium metal on the copper foil by rolling, dry and cut to obtain a negative electrode sheet.

[0128] Example 4

[0129] Different from Example 3, in this embodiment, after the negative electrode sheet is obtained in step 3, the negative electrode sheet is placed in a chemical deposition furnace, heated to 500°C and maintained in a nitrogen atmosphere, methane gas is introduced, and the reaction is carried out for 30 minutes to deposit a graphene layer on the negative electrode sheet; the thickness of the graphene layer is 1 μm.

[0130] Figure 1 This is a SEM image of the surface state of the negative electrode sheet obtained by disassembling the battery of this embodiment after 300 cycles of discharge. Figure 1 The white particles in the middle are metallic silver particles, which are evenly distributed on the surface of the electrode. Figure 2 This is the SEM image of the negative electrode sheet prepared in this embodiment. Figure 2 It can be seen that the surface of the negative electrode is uniform without protrusions or collapses.

[0131] Example 5

[0132] Different from Example 4, in this embodiment, after the negative electrode plate is obtained in step 3, the negative electrode plate is placed in a chemical deposition furnace, the temperature is raised to 800°C and maintained in a nitrogen atmosphere, methane gas is introduced, and the reaction is carried out for 20 minutes to deposit a graphene layer on the negative electrode plate, and the thickness of the graphene layer is 500nm.

[0133] Example 6

[0134] Different from Example 4, in this embodiment, after the negative electrode plate is obtained in step 3, the negative electrode plate is placed in a chemical deposition furnace, and the temperature is raised to 700°C and maintained under a nitrogen atmosphere, and methane gas is introduced and reacted for 2 hours to deposit a graphene layer on the negative electrode plate. The thickness of the graphene layer is 5 μm.

[0135] Example 7

[0136] Different from Example 3, the heat treatment temperature in step 1 of this embodiment is 800° C. and the heat treatment time is 1 hour.

[0137] Example 8

[0138] Different from Example 3, the heat treatment temperature in step 1 of this embodiment is 600° C. and the heat treatment time is 4 hours.

[0139] Example 9

[0140] Different from Example 3, the heat treatment temperature in step 1 of this embodiment is 200° C. and the heat treatment time is 30 min.

[0141] Example 10

[0142] Different from Example 3, the heat treatment temperature in step 1 of this embodiment is 1000° C. and the heat treatment time is 30 min.

[0143] Embodiment 11

[0144] Different from Example 3, the coating thickness in step 2 of this example is 10 μm.

[0145] Example 12

[0146] Different from Example 3, the coating thickness in step 2 of this example is 50 μm.

[0147] Example 13

[0148] Different from Example 3, the coating thickness in step 2 of this example is 100 μm.

[0149] Embodiment 14

[0150] Different from Example 3, the coating thickness in step 2 of this example is 0.1 μm.

[0151] Embodiment 15

[0152] Different from Example 3, the coating thickness in step 2 of this example is 1000 μm.

[0153] Example 16

[0154] Different from Example 3, in step 3 of this example, the sample is left to soak in the silver nitrate solution for 5 hours.

[0155] Embodiment 17

[0156] Different from Example 3, in step 3 of this embodiment, the sample is left to soak in the silver nitrate solution for 12 hours.

[0157] Embodiment 18

[0158] Different from Example 4, the two-dimensional layered material in this example is WS2.

[0159] Embodiment 19

[0160] Different from Example 4, the mass ratio of the two-dimensional layered material to polydopamine in this example is 55%:45%.

[0161] Embodiment 20

[0162] Different from Example 4, the mass ratio of the two-dimensional layered material to polydopamine in this example is 95%:5%.

[0163] Comparative Example 1

[0164] Different from Example 3, the two-dimensional layered material MoS2 is not used in step 1 of this comparative example.

[0165] Comparative Example 2

[0166] Different from Example 3, step 3 of this comparative example is to directly wash the copper foil coated with the first product with alcohol and water, and then dry and cut it to obtain the negative electrode sheet.

[0167] Comparative Example 3

[0168] Different from Example 3, the lithium sheet is directly used as the negative electrode sheet in this comparative example.

[0169] Comparative Example 4

[0170] Different from Example 3, step 1 of this comparative example is to mix aluminum oxide and MoS2, heat to 400°C in a nitrogen atmosphere and maintain for 30 minutes to obtain a mixed material, and place the mixed material in a sodium hydroxide solution to remove aluminum oxide to obtain a first product;

[0171] The following describes the battery performance test process and test results:

[0172] (1) Coulomb efficiency test

[0173] The assembled battery was subjected to constant current charge and discharge test at room temperature with a current density of 0.5C, and the charge capacity and discharge capacity were recorded. The coulomb efficiency is the ratio of the discharge capacity to the charge capacity.

[0174] (2) Battery cycle performance test

[0175] In an inert gas glove box where the water and oxygen content is less than 0.1ppm, the above-mentioned negative electrode plate, lithium iron phosphate (LiFePO4) positive electrode, separator, and electrolyte are assembled into a button cell. A charge and discharge cycle test is performed at a current density of 0.2C.

[0176] (3) Battery safety performance test

[0177] Place the button battery in a thermal shock test chamber, set the temperature change program, quickly heat up from room temperature to 100°C, and maintain for 0.5h, then quickly cool down to room temperature, repeat the temperature shock cycle 5 times, and check the appearance of the battery after the thermal shock test to see if there is deformation, leakage, cracking, etc.

[0178] The test results of the embodiment and comparative example batteries according to the above process and method are shown in Table 1:

[0179] Table 1 Test results of Examples 1-20 and Comparative Examples 1-4

[0180]

[0181]

[0182] According to the results shown in Table 1:

[0183] According to the test results of Examples 1-20 and Comparative Examples 1-4, the coulombic efficiency and cycle performance of the batteries of Examples 1-20 are better than those of the batteries of Comparative Examples 1-4. The composite material of Comparative Example 1 does not include a two-dimensional layered material, and the composite material of Comparative Example 2 does not include a lithium-philic metal material. After the safety performance test, although there is no swelling on the battery surface of Comparative Example 1 and Comparative Example 2, the coulombic efficiency and cycle performance of Comparative Example 1 and Comparative Example 2 are poor. Comparative Example 3 uses a lithium sheet as the negative electrode sheet, and the composite material of Comparative Example 4 does not include a carbon material. After the safety performance test, the battery surfaces of Comparative Example 3 and Comparative Example 4 are swollen, which further illustrates that the composite materials of the embodiments of the present application improve the coulombic efficiency, cycle performance and safety performance of the battery under the synergistic effect of two-dimensional materials, lithium-philic metal materials and carbon materials.

[0184] The test results of Examples 1-3 illustrate that the negative electrode sheets prepared by the method for preparing the negative electrode sheets of the embodiments of the present application and the assembled batteries all have high coulombic efficiency, good cycle stability and excellent safety performance.

[0185] The test results of Examples 3-6 show that after the graphene layer is deposited on the negative electrode sheet, the coulombic efficiency and cycle stability of the battery are improved.

[0186] The test results of Examples 7-10 illustrate that the heat treatment temperature and time of the embodiments of the present application are conducive to ensuring the reliable carbonization of the carbon material precursor while improving production efficiency. Too low a temperature will result in the inability to reliably carbonize the carbon material precursor, resulting in a decrease in the coulombic efficiency and cycle performance of the battery. Too high a temperature may destroy the structure of the two-dimensional layered material itself, resulting in a decrease in the battery cycle stability.

[0187] The test results of Examples 11 to 15 illustrate that the thickness range of the composite material of the embodiments of the present application on the surface of the current collector is conducive to ensuring that the electrolyte can reliably infiltrate the composite material, while having a suitable lithium ion transmission channel, thereby enabling the battery to have higher coulombic efficiency, cycle stability and good safety performance. Too high or too low thickness will lead to a decrease in the coulombic efficiency and cycle performance of the battery.

[0188] The test results of Example 16 and Example 17 show that the immersion time of the embodiments of the present application is conducive to the attachment of lithiophilic metal ions to the two-dimensional layered material, which is conducive to the construction of lithiophilic active sites, thereby improving the coulombic efficiency and cycle stability of the battery.

[0189] The test results of Example 18 indicate that the two-dimensional layered materials of the embodiments of the present application are all capable of improving the coulombic efficiency, cycle stability and safety performance of the battery.

[0190] The test results of Example 19 and Example 20 illustrate that the mass ratio of the two-dimensional layered material and the carbon material in the examples of the present application is conducive to ensuring that the two-dimensional layered material serves as a skeleton, thereby improving the battery's coulombic efficiency, cycle performance and safety performance.

[0191] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A composite material for lithium metal batteries, characterized in that include: Two-dimensional layered materials, carbon materials, and lithiophilic metal materials; The two-dimensional layered material comprises transition metal sulfides and / or transition metal nitrides, the lithium-philic metal material is at least distributed on the two-dimensional layered material, and the carbon material is at least coated on the surface of the two-dimensional layered material.

2. The composite material according to claim 1, characterized in that The two-dimensional layered material includes at least one of MoS2, TiS2, VS2, WS2, Bi2S3, Ga2N3, Ti2N3, and W2N3; Preferably, the mass ratio of the two-dimensional layered material to the carbon material is (60%-90%):(40%-10%).

3. The composite material according to claim 1, characterized in that The lithiophilic metal material includes Ag atom clusters.

4. The method for preparing a composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The two-dimensional layered material and the carbon material precursor are mixed and heat treated to obtain a first product; wherein the two-dimensional layered material comprises a transition metal sulfide and / or a transition metal nitride; The first product is immersed in a lithiophilic metal salt solution, and a reducing agent is added to reduce the lithiophilic metal ions to obtain a composite material.

5. A negative electrode plate, characterized in that: The invention comprises a current collector, lithium metal and the composite material according to any one of claims 1 to 3, wherein the composite material and the lithium metal are arranged on the surface of the current collector.

6. The negative electrode sheet according to claim 5, characterized in that: The thickness of the composite material on the surface of the current collector is 1 μm-100 μm; Preferably, the thickness of the lithium metal on the surface of the current collector is 0.01 μm-30 μm; Preferably, the lithium metal is distributed in the pores and / or on the surface of the composite material.

7. The negative electrode sheet according to claim 5, characterized in that: It also includes a graphene layer, which covers the surface of the composite material and / or the surface of the current collector.

8. The negative electrode sheet according to claim 7, characterized in that: The thickness of the graphene layer is 10 nm-5 μm.

9. A method for preparing a negative electrode sheet, characterized in that: include: The composite material according to any one of claims 1 to 3 or the composite material prepared by the preparation method according to claim 4 is arranged on a current collector and loaded with lithium metal to obtain the negative electrode sheet; Alternatively, a two-dimensional layered material and a carbon material precursor are mixed and heat treated to obtain a first product; wherein the two-dimensional layered material includes a transition metal sulfide and / or a transition metal nitride, the current collector to which the first product is attached is immersed in a lithium-philic metal salt solution, a reducing agent is added to reduce the lithium-philic metal ions, and lithium metal is loaded to obtain the negative electrode sheet.

10. The method according to claim 9, characterized in that The method comprises mixing the two-dimensional layered material and the carbon material precursor, and then heat treating the mixture to obtain a first product, comprising: mixing a template material and the two-dimensional layered material to obtain a mixed material; The mixed material and the carbon material precursor are mixed, heat treated, and the template material is etched with an acid solution or an alkali solution to obtain the first product.

11. The method according to claim 9, characterized in that After the two-dimensional layered material and the carbon material precursor are mixed, heat treatment is performed to obtain the first product, and the heat treatment temperature is 400°C-800°C, and the heat treatment time is 0.5h-4h.

12. The method according to claim 9, characterized in that In the process of immersing the current collector with the first product attached thereto in the lithiophilic metal salt solution, the immersion time is 1 hour to 12 hours.

13. The method according to claim 9, characterized in that The lithiophilic metal salt solution includes a silver nitrate solution, and the reducing agent includes at least one of sodium borohydride, potassium borohydride, hypophosphorous acid, sodium hypophosphite and formaldehyde.

14. The method according to claim 9, characterized in that The carbon material precursor includes at least one of polydopamine, polypyrrole, poly(3,4-ethylenedioxythiophene), polyglucose and polyvinylpyrrolidone.

15. The method according to any one of claims 9 to 14, characterized in that: After the composite material is disposed on a current collector, or after the current collector to which the first product is attached is immersed in a lithiophilic metal salt solution and a reducing agent is added to reduce the lithiophilic metal ions, the method further comprises: A graphene layer is deposited, the graphene layer covering the composite material and / or the current collector.

16. The method according to claim 15, characterized in that The depositing of the graphene layer comprises: The graphene layer is obtained by chemical vapor deposition of a carbon source in an auxiliary gas atmosphere; wherein the carbon source includes at least one of methane, acetylene, ethylene, a carbon-containing polymer material and anhydrous ethanol, and the auxiliary gas includes hydrogen, argon or nitrogen; the deposition temperature is 500°C-800°C, and the deposition time is 10min-2h.

17. A diaphragm-free battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 5 to 8, or the negative electrode sheet prepared by the method as described in any one of claims 9 to 16.

18. A lithium metal battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 5 to 8, or the negative electrode sheet prepared by the method as described in any one of claims 9 to 16.

19. An electrical equipment, characterized in that: It includes the diaphragm-free battery as described in claim 17 or the lithium metal battery as described in claim 18, and the diaphragm-free battery or the lithium metal battery supplies power to the electrical device.